Haematological studies in N'Dama, German Brown and N'Dama X Brown cows - Olusanya, S.K. (1976)
The haematological values in N'Dama, German Brown, and N'Dama x German Brown crossbreds are examined. The mean haematological values for the crossbreds were compared with those for their pure bred parents. Data on packed cell volume, haemoglobin and red blood count values, mean corpuscular volume, mean corpuscular haemoglobin concentration and white blood cell count values are included. The possibility of using haematological values of farm animals in assessing nutritional status, performance capacity, adaptability and resistance to disease should be investigated further.